Posttraumatic stress and depression symptoms as correlates of deliberate self-harm among community women experiencing intimate partner violence - Jaquier, Véronique (2012)
Deliberate self-harm (DSH) among women in the general population is correlated separately with posttraumatic stress, depression, and abuse during childhood and adulthood. The prevalence of these DSH correlates is particularly high among women exposed to intimate partner violence (IPV), yet few studies have examined DSH among this high-risk population and none have examined these correlates simultaneously. 212 IPV-victimized women in the community participated in a 2-hour retrospective interview. One-third reported current or past DSH. Discriminant analysis was used to examine which posttraumatic stress and depression symptoms and types of current IPV and childhood abuse were uniquely associated with current DSH. Findings show that women who currently use DSH reported greater severity of posttraumatic stress numbing symptoms and more severe sexual IPV compared to women who used DSH only in the past. Examining factors that are associated with women’s current DSH in this population is critical so that a focus on DSH can be integrated into the treatment plans of women who are receiving mental health care, but also so that women who are not receiving such care can be referred to adequate mental health services